Legal Protection for Women in Unregistered Polygamy: A Comparative Analysis of Polygamy Isbat - Muhammad Nasrulloh; Mohamad Zakky Ubaid Ermawan; Mohammad Fauzan Ni’ami; Moh. Toriquddin; Khoirul Anam (MUWAZAH : jurnal kajian gender, 2025)
Women involved in unregistered polygamous marriages experience compounded vulnerability, as they not only bear the social and psychological burdens of polygamy but also lose access to legal protection due to the prohibition of polygamy isbat under Supreme Court Circular Letter (SEMA) No. 3 of 2018. This restriction results in the systematic neglect of their rights as wives and citizens, including difficulties in obtaining civil registration documents, maintenance and inheritance rights, social recognition, and equitable marital relations. This study employs a normative juridical approach with descriptive analysis, utilizing statutory review and a comparative examination of legal scholars’ arguments both supporting and opposing polygamy isbat for unregistered marriages. The findings reveal a clear division among legal experts: one group advocates permitting polygamy isbat to ensure justice and legal protection for women, while the other rejects it on grounds of legal order, adherence to SEMA, and legal certainty. Based on this analysis, the study proposes two alternative solutions: first, fully opening access to polygamy isbat to promote women’s welfare; and second, adopting a selective judicial approach by granting petitions that provide substantive benefit while issuing niet ontvankelijke verklaard decisions for non-substantive cases. This study underscores the urgent need to balance substantive justice for women with the principle of legal certainty within the Indonesian family law system.